Efektifitas Konseling Terhadap Motivasi Mencegah Penularan Tb Paru Di Wilayah Puskesmas Sooko Mojokerto - Murtiyani, S.KM., S.Kep., Ns., M.Kes, Ninik; Suidah, S.Kep., Ns., M.Kes, Hartin (JURNAL KEPERAWATAN BINA SEHAT, 2017)
Pulmonary Tuberculosis (TB Lung) is an infectious disease caused by bacterium microbacterium tuberculosis where this bacteria is a very strong bacillus bacteria that require a long time to treat it. This disease is the second leading infectious disease causing death after Human Immunodeviciency Virus (HIV). WHO survey data states that 30 percent of the worlds population is infected with TB microorganisms with nine million new sufferers and three million deaths annually. Efforts to prevent transmission of pulmonary tuberculosis should be started from the desire or motivation of the pulmonary tuberculosis patients themselves so that with their consciousness they can prevent the transmission to others. The purpose of this research is to know the effectiveness of counseling to motivation to prevent transmission of Pulmonary TB in Puskesmas Sooko Mojokerto. The research design used in this research is Pre Experimental One Group Pretest Posttest Design. The sample in this research is partial pulmonary tuberculosis patients who treated for Sooko Puskemas ek as much as 32 with sampling technique of Systematc Random Sampling. Data analysis using T-test (Paired t-test) .The result of research got average value of motivation before treatment (counseling) smaller than after treatment (counseling) that is 52.66> 68.00. This mean / mean data indicates that motivation before treatment (counseling) is less good than after treatment (counseling). Counseling and counseling efforts are expected to be done as early as possible so that it can be an effort to make behavioral changes to prevent transmission of pulmonary TB. Counseling is not only done one or two times but can be continuous and not only given at the clinic but follow up can be done at home through home visits.